Comparative pharmacokinetic and relative bioavailability study of coated and uncoated azithromycin powder for suspension in healthy Bangladeshi male volunteers - Sultana, Tasmin Ara; Islam, Mohammad Safiqul; Bhuiyan, Md. Nurul Huda; Shohag, Md. Hasanuzzaman; Ahmed, Maizbha Uddin; Naznin, Sultana Rajia; Maruf, Abdullah Al; Huq, SM Imamul; Hasnat, Abul (Arzneimittelforschung, 2011)
Azithromycin (AZT; CAS 83905-01-5) is an efficient antibiotic and is widely prescribed in Bangladesh. The taste of uncoated AZT suspension is bitter. Although several taste masked oral suspensions of AZT are available in Bangladesh, information regarding the bioavailability of these formulations in Bangladeshi population is unavailable. The purpose of this study was to compare the relative bioavailability and other pharmacokinetic properties of two oral formulation of AZT (200 mg/5 ml) suspensions, the uncoated reference product and coated test product (Tridosil® 200 mg/5 ml) and to evaluate whether these formulations meet the FDA criteria to assume bioequivalence in Bangladeshi male volunteers.A randomized, single-dose, two-way cross-over, open-label pharmacokinetic study was conducted in 24 healthy male volunteers after administration of a single dose of 500 mg AZT suspension under fasting condition following a washout period of three weeks. Blood samples were collected in different time intervals and analyzed for serum AZT concentration using a validated LC/MS/MS method. The pharmacokinetic parameters were determined by the non-compartmental method. From serum data, the obtained values for test and reference products were 383.21 ± 11.59 and 432.28 ± 7.22 ng/ml for Cmax; 5677.47 ± 1229.53 and 6144.56 ± 1098.70 h · ng/ml for AUC0–120; and 6085.29 ± 1267.53 and 6694.15 ± 1222.50 h · ng/ml for AUC0–∞, respectively. On analysis of variance, no period or sequence effects were observed for any pharmacokinetic property; however, a significant formulation effect was observed for Cmax and AUMC0–∞. The 90% confidence intervals of the test formulation/reference mean ratios of the In-transformed Cmax, AUC0–120 and AUC0–∞ mean values were found to be 87.89% to 89.36%, 87.96% to 95.71% and 86.77% to 94.29% respectively. In this single-dose study of AZT, it was found that the test formulation met the regulatory criteria for bioequivalence to the reference suspension formulation.
Keywords: Azithromycin; Bioequivalence; Clarithromycin; LC/MS/MS; Macrolide antibiotic; Pharmacokinetics